Baśniowe przestrzenie działania z perspektywy przyszłych nauczycieli - Magdalena Kaliszewska-Henczel (Problemy Wczesnej Edukacji)
The aim of the article is to present meanings associated with fairy tale places by teacher candidates. The research data came from interviews with 57 early childhood pedagogy students, analysed through a qualitative method. The competences of candidates for teachers in perceiving the symbolism of places, wandering, world layout, reveal not only the level of cultural and literary knowledge (because they are a “showcase” of previous school experiences of fairy-tale themed lessons), but also indicate their future strategies for designing children’s activity based on fairy tales. These strategies may turn out to be so durable and resistant to change that they might survive university literary education and remain the starting point for students’ teaching practice. The research shows that the fairy tale can remain in them as the starting point for fun or a “background” for science, mathematics and language.